Hemodialysis membrane with self-anticoagulation function and preparation method thereof
By modifying the hemodialysis membrane with natural polymer fibrin, polydopamine and sulfonic acid polymers, the problems of poor biocompatibility and insufficient anticoagulation performance of the hemodialysis membrane are solved, and good hemocompatibility and low hemolysis rate of the modified membrane are achieved, effectively avoiding thrombosis and improving the quality of life of patients.
Patent Information
- Application Number
- CN202510141199.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-22
AI Technical Summary
The existing hemodialysis membrane has poor biocompatibility and insufficient anticoagulation performance, which leads to prone to coagulation reactions during hemodialysis, increasing the risk of bleeding and thrombosis in patients.
By modifying the hemodialysis membrane with natural polymer fibrin, polydopamine and sulfonic acid polymer, a membrane surface with self-anticoagulation function is formed, and the biocompatibility and anticoagulation properties of the membrane are improved.
The modified hemodialysis membrane shows good hemocompatibility in inhibiting protein adsorption, platelet adsorption, and red blood cell adsorption, low hemolysis rate, prolongs coagulation time, effectively avoids thrombosis, and improves the patient's quality of life and survival time.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hemodialysis membranes, and in particular to a hemodialysis membrane with self-anticoagulation function and a preparation method thereof. Background Art
[0002] Hemodialysis is the most widely used blood purification technology in clinical practice and one of the renal replacement therapies for patients with acute and chronic renal failure. It mainly uses the principle of semipermeable membrane to remove various harmful substances, excess electrolytes and metabolic waste from the patient's body through diffusion, adsorption, ultrafiltration, convection, etc., in order to purify the blood, correct acid-base balance and water and electrolyte disorders. However, during hemodialysis, the large amount of contact between the dialysis membrane and non-biological substances in the blood may cause a series of biocompatibility problems, such as activation of the coagulation system, complement activation, platelet activation, etc.
[0003] Anticoagulation is a basic measure to ensure the effectiveness and safety of blood purification. Traditional hemodialysis membranes are mostly made of polyacrylonitrile, polysulfone, polyethersulfone, polypropylene and other materials, but their own anticoagulant properties are poor and require additional anticoagulation treatment. Anticoagulants such as heparin are usually used during dialysis to prevent coagulation, but improper use of anticoagulants may increase the patient's risk of bleeding and thrombosis, and may also cause adverse reactions such as allergies, rashes, fever, and difficulty breathing. How to ensure the effectiveness and safety of the hemodialysis process without using anticoagulants or reducing the amount of anticoagulants used is an urgent problem to be solved.
[0004] The poor biocompatibility of existing hemodialysis membranes is mainly due to factors such as poor surface hydrophilicity, uneven charge, and lack of anchoring sites for anticoagulant active molecules, which makes blood components easy to activate and aggregate on the membrane surface, thereby inducing a coagulation reaction. Therefore, it is particularly important to modify the hemodialysis membrane to improve its blood compatibility, especially its anticoagulant performance. Summary of the invention
[0005] The purpose of the present invention is to provide a hemodialysis membrane with self-anticoagulation function and a preparation method thereof, so as to solve the problems of poor biocompatibility and insufficient anticoagulation performance of the hemodialysis membrane in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a hemodialysis membrane with self-anticoagulation function. The hemodialysis membrane is modified by natural high-molecular fibrin, polydopamine and sulfonic acid polymer solution to obtain the hemodialysis membrane with self-anticoagulation function. The hemodialysis membrane is any one or any combination of polysulfone membrane, polyethersulfone membrane, polyvinylidene fluoride membrane, polymethyl methacrylate membrane, polyacrylonitrile membrane, polyamide membrane, polyvinyl alcohol membrane, cellulose acetate membrane and polypropylene membrane.
[0007] Furthermore, the natural polymer fibrous protein is any one or any combination of fibroin, sericin, and collagen.
[0008] Furthermore, the sulfonic acid polymer is any one or any combination of sodium styrene sulfonate-maleic anhydride copolymer, sodium polystyrene sulfonate, polystyrene sulfonic acid, sulfonated chitosan, and methane sulfonate-polyethylene glycol-methane sulfonate copolymer.
[0009] The present invention also provides a method for preparing a hemodialysis membrane having a self-anticoagulation function, comprising the following steps: S1, hemodialysis membrane pretreatment; S2, preparing a natural polymer fibrin-polydopamine composite solution; S3, preparing a sulfonic acid polymer solution; S4, at a constant temperature, passing the natural polymer fibrin-polydopamine composite solution in S2 through a hemodialysis membrane to obtain a natural polymer fibrin-polydopamine modified hemodialysis membrane; S5. Under constant temperature, the sulfonic acid polymer solution in S3 is passed through the natural polymer fibrin-polydopamine modified hemodialysis membrane in S4 to obtain a natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane.
[0010] Furthermore, the pretreatment in S1 is specifically as follows: soaking the hemodialysis membrane in anhydrous ethanol for 0.5 to 2 hours, then soaking it in purified water for 0.5 to 2 hours, repeating this process 2 to 4 times, and placing it in purified water for standby use.
[0011] Furthermore, the S2 comprises the following sub-steps: S21, dissolving natural polymer fibrin in a ternary solution consisting of neutral salt-solvent-purified water, wherein the molar ratio of the ternary substances is 1:2:7-6:3:1, and the dissolution temperature is 60° C.-90° C.; S22, dialyze in purified water for 48-72 hours, the molecular weight cutoff of the dialysis bag is 3000-20000, the water is changed every 2-8 hours, the dialyzed solution is centrifuged for 10-30 minutes, the centrifugal temperature is 0°C-8°C, the centrifugal speed is 6000-10000 rpm to remove the residue, and obtain a natural high molecular fibrin solution with a concentration of 2-20wt.%; S23. Take dopamine hydrochloride and add it to the natural polymer fibrin solution and mix evenly. The dopamine concentration is 4-20 wt.%. Add sodium hydroxide to adjust the solution pH to 8-9. Let stand at 20°C-40°C for 24-72 hours to allow the dopamine in the solution to spontaneously polymerize to obtain a natural polymer fibrin-polydopamine composite solution.
[0012] Furthermore, the neutral salt is any one of magnesium nitrate, lithium bromide, and calcium chloride; and the solvent is any one of methanol, ethanol, and dimethyl sulfoxide.
[0013] Furthermore, S3 is specifically as follows: 3-70 parts of sulfonic acid polymer, 0.5-5 parts of surfactant, and 25-96.5 parts of purified water are taken, and stirred and dissolved at a temperature of 50° C. to 80° C. for 4-24 hours to obtain a sulfonic acid polymer solution.
[0014] Furthermore, the surfactant is any one or any combination of polyoxyethylene polyoxypropylene ether block copolymer and alkylphenol polyoxyethylene ether.
[0015] Furthermore, the constant temperature in S4 and S5 is 20° C. to 40° C., and the time for the solution to flow through the dialysis membrane is 60 to 240 minutes.
[0016] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects: The present invention provides a hemodialysis membrane with self-anticoagulation function, which is used for the treatment of acute and chronic kidney diseases, has good biocompatibility, and exhibits good blood compatibility in terms of inhibiting protein adsorption, platelet adsorption, red blood cell adsorption, low hemolysis rate, prolonged coagulation time, etc. It can effectively avoid the risk of thrombosis caused by improper use of anticoagulants during continuous anticoagulation treatment, and effectively improve the quality of life and survival time of hemodialysis patients.
[0017] The present invention provides a hemodialysis membrane with self-anticoagulation function and a preparation method thereof, and uses natural high-molecular fibrin-polydopamine and sulfonic acid polymer to carry out functional modification on the membrane surface.
[0018] (1) Natural polymer fibrin is a natural biopolymer that is non-toxic, non-sensitizing and non-irritating to the human body and has excellent biocompatibility and hydrophilicity. The protein molecules contain active groups such as hydroxyl and amine groups, which can not only provide excellent hydrophilicity for the membrane surface, but also form hydrogen bonds and electrostatic interactions with polydopamine and sulfonic acid polymers, thereby better combining the components in the composite solution to form a stable structure.
[0019] (2) Dopamine has multiple functional structures such as catechol, amine, and imine, and has excellent biocompatibility. It will spontaneously polymerize under weak alkaline conditions to form random polymer polydopamine. Polydopamine has a large number of hydrogen bond donor / acceptor units, which can be combined with natural polymer fibrin and sulfonic acid polymer chains through hydrogen bonds and electrostatic interactions. Its high adhesion enables the complex to firmly adhere to the surface of the hemodialysis membrane, improving the stability of the coating.
[0020] (3) The sulfonic acid groups in the sulfonic acid polymer can make the surface of the material negatively charged, interact with the components in the blood, reduce the adhesion of platelets and the activation of coagulation factors, especially the coagulation factors FVIII and FXII of the intrinsic coagulation system, and reduce the risk of thrombosis. Its hydrophilicity helps to reduce protein adsorption, thereby further improving the blood compatibility of the hemodialysis membrane. The hydrophilic layer is constructed on the surface of the hemodialysis membrane by the surface immersion coating method, thereby achieving hydrophilization of the membrane surface, which is easy to operate. DETAILED DESCRIPTION
[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0022] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0023] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0024] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0026] Example 1 (1) Pretreatment of hemodialysis membrane: Soak the polyethersulfone membrane in anhydrous ethanol for 0.5 to 1 hour, then soak it in purified water for 0.5 to 1 hour, and repeat this process three times. After treatment, place it in purified water for later use.
[0027] (2) Preparation of natural polymer fibrin-polydopamine composite solution: Silk fibroin was dissolved in a ternary solution of calcium chloride-dimethyl sulfoxide-purified water, the molar ratio of the ternary substances was 1:2:7, and the dissolution temperature was 80°C. The solution was dialyzed in purified water for 70 hours, the molecular weight cutoff of the dialysis bag was 4000-15000, and the water was changed every 4 hours. The dialyzed solution was centrifuged for 25 minutes at a centrifugal temperature of 3°C and a centrifugal speed of 8000 rpm to remove the residue to obtain a silk fibroin solution with a concentration of 15 wt.%. Dopamine hydrochloride was added to the silk fibroin solution and mixed evenly, the dopamine concentration was 6 wt.%, and sodium hydroxide was added to adjust the solution pH to 8.5. The solution was allowed to stand at 40°C for 48 hours to allow the dopamine in the solution to spontaneously polymerize, thereby obtaining a silk fibroin-polydopamine composite solution.
[0028] (3) Preparation of sulfonic acid polymer solution: Take 45 parts of sodium polystyrene sulfonate, 1.5 parts of polyoxyethylene polyoxypropylene ether block copolymer, and 53.5 parts of purified water, stir and dissolve them at a temperature of 70-80°C for 24 hours to prepare a sodium polystyrene sulfonate solution.
[0029] (4) Preparation of natural polymer fibrin-polydopamine modified hemodialysis membrane: Under a constant temperature of 30°C, the silk fibroin-polydopamine composite solution was passed through the pretreated polyethersulfone hemodialysis membrane for a flow time (reaction time) of 200 minutes to obtain a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane.
[0030] (5) Preparation of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: Under a constant temperature of 30°C, a sodium polystyrene sulfonate solution was passed through a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane for 200 minutes (reaction time), thereby obtaining a silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane.
[0031] (6) Post-treatment of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: The silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane was repeatedly rinsed with purified water for 5 minutes to remove the silk fibroin, polydopamine and sodium polystyrene sulfonate that were not firmly bound to the surface. Finally, the modified hemodialysis membrane was naturally dried.
[0032] Example 2 (1) Pretreatment of hemodialysis membrane: Soak the polyethersulfone membrane in anhydrous ethanol for 0.5 to 1 hour, then soak it in purified water for 0.5 to 1 hour, and repeat this process three times. After treatment, place it in purified water for later use.
[0033] (2) Preparation of natural polymer fibrin-polydopamine composite solution: Dissolve silk fibroin in a ternary solution consisting of calcium chloride-ethanol-purified water, the molar ratio of the ternary substances is 6:3:1, and the dissolution temperature is 80°C. Dialyze in purified water for 70 hours, the molecular weight cutoff of the dialysis bag is 4000-15000, and the water is changed every 4 hours. The dialyzed solution is centrifuged for 25 minutes at a centrifugal temperature of 3°C and a centrifugal speed of 8000 rpm to remove the residue to obtain a silk fibroin solution with a concentration of 10 wt.%. Take dopamine hydrochloride and add it to the silk fibroin solution and mix evenly. The dopamine concentration is 10 wt.%. Sodium hydroxide is added to adjust the solution pH to 8.5. Let it stand at 40°C for 48 hours to allow the dopamine in the solution to spontaneously polymerize to obtain a silk fibroin-polydopamine composite solution.
[0034] (3) Preparation of sulfonic acid polymer solution: Take 38 parts of sodium polystyrene sulfonate, 0.6 parts of polyoxyethylene polyoxypropylene ether block copolymer, and 61.4 parts of purified water, stir and dissolve them at a temperature of 70-80°C for 24 hours to prepare a sodium polystyrene sulfonate solution.
[0035] (4) Preparation of natural polymer fibrin-polydopamine modified hemodialysis membrane: Under a constant temperature of 30°C, the silk fibroin-polydopamine composite solution was passed through the pretreated polyethersulfone hemodialysis membrane for a flow time (reaction time) of 150 minutes to obtain a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane.
[0036] (5) Preparation of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: Under a constant temperature of 30°C, a sodium polystyrene sulfonate solution was passed through a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane for 150 minutes to obtain a silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane.
[0037] (6) Post-treatment of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: The silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane was repeatedly rinsed with purified water for 3 minutes to remove the silk fibroin, polydopamine and sodium polystyrene sulfonate that were not firmly bound to the surface. Finally, the modified hemodialysis membrane was naturally dried.
[0038] Example 3 (1) Pretreatment of hemodialysis membrane: Soak the polyethersulfone membrane in anhydrous ethanol for 0.5 to 1 hour, then soak it in purified water for 0.5 to 1 hour, and repeat this process three times. After treatment, place it in purified water for later use.
[0039] (2) Preparation of natural polymer fibrin-polydopamine composite solution: Dissolve silk fibroin in a ternary solution of calcium chloride-ethanol-purified water, the molar ratio of the ternary substances is 2:5:3, and the dissolution temperature is 80°C. Dialyze in purified water for 70 hours, the molecular weight cutoff of the dialysis bag is 4000-15000, and the water is changed every 4 hours. The dialyzed solution is centrifuged for 25 minutes at a centrifugal temperature of 3°C and a centrifugal speed of 8000 rpm to remove the residue to obtain a silk fibroin solution with a concentration of 3 wt.%. Take dopamine hydrochloride and add it to the silk fibroin solution and mix evenly. The dopamine concentration is 5 wt.%. Sodium hydroxide is added to adjust the solution pH to 8.5. Let it stand at 40°C for 48 hours to allow the dopamine in the solution to spontaneously polymerize to obtain a silk fibroin-polydopamine composite solution.
[0040] (3) Preparation of sulfonic acid polymer solution: Take 32 parts of sodium polystyrene sulfonate, 0.3 parts of polyoxyethylene polyoxypropylene ether block copolymer, and 67.7 parts of purified water, stir and dissolve them at a temperature of 70-80°C for 24 hours to prepare a sodium polystyrene sulfonate solution.
[0041] (4) Preparation of natural polymer fibrin-polydopamine modified hemodialysis membrane: Under a constant temperature of 30°C, the silk fibroin-polydopamine composite solution was passed through the pretreated polyethersulfone hemodialysis membrane for a flow time (reaction time) of 150 minutes to obtain a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane.
[0042] (5) Preparation of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: Under a constant temperature of 30°C, a sodium polystyrene sulfonate solution was passed through a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane for 150 minutes to obtain a silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane.
[0043] (6) Post-treatment of natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane: The silk fibroin-polydopamine-sodium polystyrene sulfonate modified polyethersulfone hemodialysis membrane was repeatedly rinsed with purified water for 3 minutes to remove the silk fibroin, polydopamine and sodium polystyrene sulfonate that were not firmly bound to the surface. Finally, the modified hemodialysis membrane was naturally dried.
[0044] Example 4 The difference from Example 1 is: The polyethersulfone membrane is replaced by one of a polysulfone membrane, a polyvinylidene fluoride membrane, a polymethyl methacrylate membrane, a polyacrylonitrile membrane, a polyamide membrane, a polyvinyl alcohol membrane, a cellulose acetate membrane, and a polypropylene membrane; Replace calcium chloride with magnesium nitrate; Replacing sodium polystyrene sulfonate with one or more of sodium styrene sulfonate-maleic anhydride copolymer, sodium polystyrene sulfonate, polystyrene sulfonic acid, sulfonated chitosan, and methanesulfonate-polyethylene glycol-methanesulfonate copolymer; The rest of the process was carried out according to Example 1.
[0045] Example 5 The difference from Example 1 is: Replacing silk fibroin with any one or any combination of silk fibroin, sericin, and collagen; Replace calcium chloride with lithium bromide; The rest of the process was carried out according to Example 1.
[0046] Comparative Example 1 Polyethersulfone hemodialysis membrane was not modified.
[0047] Comparative Example 2 The polyethersulfone hemodialysis membrane is only modified by the natural polymer fibrin-polydopamine.
[0048] (1) Pretreatment of hemodialysis membrane: Soak the polyethersulfone membrane in anhydrous ethanol for 0.5 to 1 hour, then soak it in purified water for 0.5 to 1 hour, and repeat this process three times. After treatment, place it in purified water for later use.
[0049] (2) Preparation of natural polymer fibrin-polydopamine composite solution: Silk fibroin was dissolved in a ternary solution of calcium chloride-dimethyl sulfoxide-purified water, the molar ratio of the ternary substances was 1:2:7, and the dissolution temperature was 80°C. The solution was dialyzed in purified water for 70 hours, the molecular weight cutoff of the dialysis bag was 4000-15000, and the water was changed every 4 hours. The dialyzed solution was centrifuged for 25 minutes at a centrifugal temperature of 3°C and a centrifugal speed of 8000 rpm to remove the residue to obtain a silk fibroin solution with a concentration of 15 wt.%. Dopamine hydrochloride was added to the silk fibroin solution and mixed evenly, the dopamine concentration was 6 wt.%, and sodium hydroxide was added to adjust the solution pH to 8.5. The solution was allowed to stand at 40°C for 48 hours to allow the dopamine in the solution to spontaneously polymerize, thereby obtaining a silk fibroin-polydopamine composite solution.
[0050] (3) Preparation of natural polymer fibrin-polydopamine modified hemodialysis membrane: Under a constant temperature of 30°C, the silk fibroin-polydopamine composite solution was passed through the pretreated polyethersulfone hemodialysis membrane for a flow time (reaction time) of 200 minutes to obtain a silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane.
[0051] (4) Post-treatment of natural polymer fibrin-polydopamine modified hemodialysis membrane: The silk fibroin-polydopamine modified hemodialysis membrane was repeatedly rinsed with purified water for 5 minutes to remove the silk fibroin and polydopamine that were not firmly bound to the surface. Finally, the modified hemodialysis membrane was naturally dried.
[0052] The hemodialysis membranes of Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, and the results are shown in Table 1: Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Activated partial thromboplastin time (s) 110.2 82.4 67.5 35.5 65.6 Prothrombin time (s) 17.5 16.8 16.3 15.1 15.9 Thrombin time (s) 21.2 20.1 19.5 17.6 19.8 Fibrinogen (g / L) 3.27 3.32 3.45 4.02 3.41 Hemolysis rate (%) 1.58 1.67 1.85 3.20 1.88 The performance test results of Examples 4-5 are close to those of Example 1 (not shown in the table).
[0053] It can be seen from Table 1 that compared with the unmodified polyethersulfone hemodialysis membrane of Comparative Example 1, the anticoagulant modification of the hemodialysis membrane with self-anticoagulant function obtained in Examples 1-3 can inhibit both endogenous and exogenous coagulation pathways, and can significantly prolong the activated partial thromboplastin time, prolong the prothrombin time and the thrombin time. The active groups such as hydroxyl groups and amine groups on the surface of the modified hemodialysis membrane can form hydrogen bonds with fibrinogen, so that the adsorption of fibrinogen on the membrane surface is higher, and the fibrinogen involved in coagulation is reduced, thereby inhibiting coagulation. Therefore, the surface of the modified hemodialysis membrane prepared in Examples 1-3 has enhanced self-anticoagulability, especially the surface of the modified hemodialysis membrane prepared in Example 1, after contact with blood, its activated partial thromboplastin time is extended by about 3 times compared to the modified hemodialysis membrane.
[0054] Comparative Example 2 only uses silk fibroin-polydopamine to modify polyethersulfone hemodialysis membrane, which still shows good anti-coagulation performance of the membrane, but the silk fibroin-polydopamine modified polyethersulfone hemodialysis membrane further modified with sodium polystyrene sulfonate has a more obvious improvement in effect. It can be seen that the natural polymer fibrin, dopamine, and sulfonic acid polymer in the present invention form a compounding effect, which significantly improves the effect of the hemodialysis membrane after modification.
[0055] Finally, it should be noted that: The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hemodialysis membrane with self-anticoagulation function, characterized in that: The hemodialysis membrane is modified by natural polymer fibrin, polydopamine and sulfonic acid polymer solution to obtain a hemodialysis membrane with self-anticoagulation function. The hemodialysis membrane is any one or any combination of polysulfone membrane, polyethersulfone membrane, polyvinylidene fluoride membrane, polymethyl methacrylate membrane, polyacrylonitrile membrane, polyamide membrane, polyvinyl alcohol membrane, cellulose acetate membrane and polypropylene membrane.
2. The hemodialysis membrane with self-anticoagulation function according to claim 1, characterized in that: The natural high molecular weight fibrous protein is any one or any combination of fibroin, sericin and collagen.
3. The hemodialysis membrane with self-anticoagulation function according to claim 1, characterized in that: The sulfonic acid polymer is any one or any combination of sodium styrene sulfonate-maleic anhydride copolymer, sodium polystyrene sulfonate, polystyrene sulfonic acid, sulfonated chitosan, and methane sulfonate-polyethylene glycol-methane sulfonate copolymer.
4. The method for preparing a hemodialysis membrane having self-anticoagulation function according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Pretreatment of hemodialysis membrane: soak the hemodialysis membrane in anhydrous ethanol for 0.5 to 2 hours, then soak it in purified water for 0.5 to 2 hours, repeat 2 to 4 times, and place it in purified water for standby use; S2, preparing a natural polymer fibrin-polydopamine composite solution; S3, preparing a sulfonic acid polymer solution; S4, at a constant temperature, passing the natural polymer fibrin-polydopamine composite solution in S2 through a hemodialysis membrane to obtain a natural polymer fibrin-polydopamine modified hemodialysis membrane; S5. Under constant temperature, the sulfonic acid polymer solution in S3 is passed through the natural polymer fibrin-polydopamine modified hemodialysis membrane in S4 to obtain a natural polymer fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane.
5. The method for preparing a hemodialysis membrane having self-anticoagulation function according to claim 4, characterized in that: The S2 comprises the following sub-steps: S21, dissolving natural polymer fibrin in a ternary solution consisting of neutral salt-solvent-purified water, wherein the molar ratio of the ternary substances is 1:2:7-6:3:1, and the dissolution temperature is 60° C.-90° C.; S22, dialyze in purified water for 48-72 hours, the molecular weight cutoff of the dialysis bag is 3000-20000, the water is changed every 2-8 hours, the dialyzed solution is centrifuged for 10-30 minutes, the centrifugal temperature is 0°C-8°C, the centrifugal speed is 6000-10000 rpm to remove the residue, and obtain a natural high molecular fibrin solution with a concentration of 2-20wt.%; S23. Take dopamine hydrochloride and add it to the natural polymer fibrin solution and mix evenly. The dopamine concentration is 4-20wt.%, and sodium hydroxide is added to adjust the solution pH to 8-9. The solution is allowed to stand at 20°C-40°C for 24-72 hours to allow the dopamine in the solution to spontaneously polymerize, thereby obtaining a natural polymer fibrin-polydopamine composite solution.
6. The method for preparing a hemodialysis membrane having self-anticoagulation function according to claim 5, characterized in that: The neutral salt is any one of magnesium nitrate, lithium bromide and calcium chloride; the solvent is any one of methanol, ethanol and dimethyl sulfoxide.
7. The method for preparing a hemodialysis membrane having self-anticoagulation function according to claim 4, characterized in that: The S3 is specifically as follows: 3-70 parts of sulfonic acid polymer, 0.5-5 parts of surfactant, and 25-96.5 parts of purified water are taken, and stirred and dissolved at a temperature of 50° C. to 80° C. for 4-24 hours to obtain a sulfonic acid polymer solution.
8. The method for preparing a hemodialysis membrane having self-anticoagulation function according to claim 7, characterized in that: The surfactant is any one or any combination of polyoxyethylene polyoxypropylene ether block copolymer and alkylphenol polyoxyethylene ether.
9. The method for preparing a hemodialysis membrane having self-anticoagulation function according to claim 4, characterized in that: The constant temperature in S4 and S5 is 20° C. to 40° C., and the time for the solution to flow through the dialysis membrane is 60 to 240 minutes.
10. The method for preparing a hemodialysis membrane with self-anticoagulation function according to claim 4, characterized in that: The method also includes post-processing of the obtained natural high-molecular fibrin-polydopamine-sulfonic acid polymer modified hemodialysis membrane, and the post-processing includes flushing and drying.
Citation Information
Cited By
Super-hydrophilic polyethersulfone hollow fiber membrane as well as preparation method and application thereof
CN121422757A